Crescimento e caracterização óptica de cristais de L-Asparagina pura e L-Asparagina irradiada - Fujita, Alessandra Keiko Lima (2012)
In this work we present the results of L-asparagine H2O crystal growth and the study of their optical properties, linear and nonlinear, of crystal as grown and after being submitted to high doses of X-ray. Crystals were grown in aqueous solution by the method of slow evaporation of the solvent. Measurements optical absorption, Raman, thermal analysis and efficiency of second harmonic generation were carried out. The results demonstrate the good optical quality of the crystals for use in optical devices, comparable to that of KDP (KH2PO4). .